IFN-γ enhances protective efficacy against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Yu, Ruying; Zhang, Weixiang; Yu, Penghui; Zhou, Jiancheng; Su, Jianguo; Yuan, Gailing (Frontiers in Immunology, 2024)
Introduction Nocardia seriolae adversely impacts a diverse range of fish species, exhibiting significant pathogenic characteristics that substantially impede the progress of aquaculture. N. seriolae infects in fish has a long incubation period, and clinical symptoms are not obvious in the early stages. There is presently no viable and eco-friendly approach to combat the spread of the disease. According to reports, N. seriolae primarily targets macrophages in tissues after infecting fish and can proliferate massively, leading to the death of fish. Interferon-gamma (IFN-γ) is a crucial molecule that regulates macrophage activation, but little is known about its role in the N. seriolae prevention. Methods IFN-γ was first defined as largemouth bass (Micropterus salmoides, MsIFN-γ), which has a highly conserved IFN-γ characteristic sequence through homology analysis. The recombinant proteins (rMsIFN-γ) were obtained in Escherichia coli (E. coli) strain BL21 (DE3). The inflammatory response-inducing ability of rMsIFN-γ was assessed in vitro using monocytes/macrophages. Meanwhile, the protective effect of MsIFN-γ in vivo was evaluated by N. seriolae infection largemouth bass model. Results In the inflammatory response of the monocytes/macrophages activated by rMsIFN-γ, various cytokines were significantly increased. Interestingly, interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF-a) increased by 183- and 12-fold, respectively, after rMsIFN-γ stimulation. rMsIFN-γ improved survival by 42.1% compared with the control. The bacterial load in the liver, spleen and head kidney significantly decreased. rMsIFN-γ was also shown to better induce increased expression of IL-1β, TNF-α, hepcidin-1(Hep-1), major histocompatibility complex I (MHCI), and MHC II in head kidney, spleen and liver. The histopathological examination demonstrated the transformation of granuloma status from an early necrotic foci to fibrosis in the infection period. Unexpectedly, the development of granulomas was successfully slowed in the rMsIFN-γ group. Discussion This work paves the way for further research into IFN-γ of largemouth bass and identifies a potential therapeutic target for the prevention of N. seriolae.